The function of dietary phenolic acids in cardiovascular health - Aidilla Mubarak (Australia: The University of Western Australia, 2014)
Dietary phenolics have been associated with protection against the various forms of cardiovascular disease (CVD). This thesis outlines three independent studies, from analytical to intervention, which increase our knowledge on the role of phenolic compounds in preventative health. Particular attention was paid to phenolics found in fruit, as they are a rich source and widely available and consumed, and hence make a large contribution to dietary phenolics intake.